GLOBALISASI DAN HAK ASASI MANUSIA (HAM): STUDI KASUS PELANGGARAN HAM DI MYANMAR - Verdinand Robertua (Sociae Polites, 2015)
AbstractThis article is a conceptual review focusing theinterrelatedness of globalization and human rights.Myanmar governments has been accused ofexploiting Myanmarâ€™s human rights and Europeangovernments has applied sanctions andcondemnations toward Myanmar. The researchquestion is how human rights value internalize toMyanmar in the context of globalization. Toanswer this question, the author used EnglishSchool Theory pioneered by Hedley Bull and BarryBuzan. Since this is a value debate, three conceptsof English School will be used as value comparisonwhich are international order, pluralism andsolidarism. Through comparative study of values,this article concluded that universalization ofhuman rights through sanctions provokedresistance from ASEAN countries. National andlocal values of ASEAN countries such as sovereigntyand order have balanced the human rights value.â€œASEAN Wayâ€ is symbol of balanced interactionbetween global and local values. Coexistence, a keyconcept of English School, become a key conceptrelevant in discussing the interrelatedness ofglobalization and human rights in the context ofMyanmar.Keywords: Globalization, Human Rights, EnglishSchool, Pluaralism, Solidarism, International Order,ASEAN, Myanmar AbstrakArtikel ini merupakan kajian konseptual membahasketerkaitan antara fenomena globalisasi dankonsep hak asasi manusia melalui studi kasuspelanggaran HAM di Myanmar. Tindakan dankebijakan Pemerintah Myanmar dianggapmerampas hak asasi manusia Myanmar danmemicu kemarahan dan sanksi ekonomi dari UniEropa Eropa. Pertanyaan yang diangkat adalahbagaimana penyebaran nilai HAM dalam konteksglobalisasi dengan studi kasus Myanmar. Untukmenjawab pertanyaan ini, penulis menggunakanteori English School of International Relation yangdigagas oleh Hedley Bull dan Barry Buzan. Dalammelihat perdebatan nilai HAM ini, terdapat tigakonsep English School untuk menjadi studiperbandingan nilai yaitu tatanan internasional,pluralism dan solidarisme. Melalui studiperbandingan nilai ini, penulis berkesimpulanbahwa globalisasi nilai HAM melalui instrumensanksi yang diterapkan Uni Eropa menghasilkanresistensi dari negara-negara ASEAN dan terciptainteraksi yang lebih berimbang denganmemperhatikan nilai-nilai yang diadopsi negaranegaraASEAN. Coexistence yang diajukan konseppluralisme dalam bentuk â€œASEAN Wayâ€ menjadirelevan dalam perdebatan nilai HAM di Myanmar.Kata kunci: Globalisasi, Hak Asasi Manusia, EnglishSchool, Pluralisme, Solidarisme, TatananInternasional, ASEAN, Myanmar